(untitled) (Carte Romanze, 2018)
Cette contribution présente l’édition critique de la Passion de saint Adrian de Jean Miélot et illustre, par une présentation de la tradition manuscrite et une analyse des techniques de traduction, l’intérêt de cette œuvre. La contex- tualisation de la Passion dans le cadre de la production de Miélot permet également d’esquisser un rapide bilan sur son corpus hagiographique. This contribution provides a preliminary study to the critical edition of the Passion de saint Adrian by Jean Miélot and shows, through a presentation of the manuscript tradition and an analysis of translation techniques, the interest of this work. The contextualization of this text as part of Miélot production also makes possible to sketch a rapid assessment of his hagiographic corpus.